The Axiological Price of Development - Olivier, Bert (International Journal of Psychosocial Rehabilitation, 2019)
This paper examines certain disturbing cultural trends in the United States, such as mass shootings and the phenomenon of ‘gutterpunks’—young p people from affluent homes who have chosen to live ‘homelessly’ on streets in American cities. The question is raised, what it is that is missing from these young people’s lives, given the valorization of material wealth in America and the western world generally. In the final analysis, the paper is a (brief) investigation of the question concerning the values that make life worth living, and the claim is made that ‘empty materialism,’ as evidenced in several cultural phenomena scrutinized here, does not embody a viable set of values.